2011
DOI: 10.1111/j.1471-6712.2011.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐care ability among home‐dwelling older people in rural areas in southern Norway

Abstract: When self-care ability is reduced in older people, caregivers have to be aware about how this can be expressed and also be aware of their responsibility for identifying and mapping needs for appropriate support and help, and preventing unnecessary and unwanted dependency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 57 publications
(87 reference statements)
9
60
1
3
Order By: Relevance
“…They saw both physical and mental activities as important for maintaining health and well-being, and being active has been shown to be a productive means for self-care among older home-dwelling people in other studies 23,34. This is also in line with a study among middle-aged individuals about their transition into retirement, where it was shown that participants saw old-age pensioner life, when being in good health, as a time of opportunities: retirement could give a sense of freedom and motivation for being active 35…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…They saw both physical and mental activities as important for maintaining health and well-being, and being active has been shown to be a productive means for self-care among older home-dwelling people in other studies 23,34. This is also in line with a study among middle-aged individuals about their transition into retirement, where it was shown that participants saw old-age pensioner life, when being in good health, as a time of opportunities: retirement could give a sense of freedom and motivation for being active 35…”
Section: Discussionmentioning
confidence: 89%
“…Since no official cutoff point is recommended for this type of sample in the literature, a SOC score ranging from 153 to 203 – that is, a value that was higher than the mean value of 152 in the survey study23 – was considered to be a strong SOC. This is also in line with normative data from other studies 2.…”
Section: Methodsmentioning
confidence: 99%
“…Sundsli et al (2012) found a higher risk amongst adults aged ≥85 years with a mean NUFFE score of 6.6 ±4.1, which is in the at risk category; whilst the mean score of total participants aged ≥65 years was in the low risk category (4.0 ± 3.1). Poorer self-care ability was found in the at risk group and associated with inability to prepare food (Dale et al, 2012). Identified contributors to nutrition risk were receiving assistance for daily living, being inactive, displaying a sense of helplessness and living alone (Tomstad et al, 2012).…”
Section: Nutritional Form For the Elderly (Nuffe)mentioning
confidence: 99%
“…Three studies were conducted in Norway (Dale et al, 2012;Sundsli et al, 2012;Tomstad et al, 2012) and one in Sweden . Approximately 80% of older adults were identified as well-nourished according to NUFFE classification Tomstad et al, 2012).…”
Section: Nutritional Form For the Elderly (Nuffe)mentioning
confidence: 99%
“…This influences older people’s daily life13 and higher self-care ability supports personal health in later life. A strong relationship between lower self-care ability and being at risk of undernutrition has also been shown 2,14. A significant association between unintended weight loss and impaired function regarding activities of daily living has been reported among older people living at home 9…”
Section: Introductionmentioning
confidence: 98%